Mission and vision in industry development / Baderisang Mohamed and Nurul Amira Ahmad Murad - Mohamed, Baderisang; Ahmad Murad, Nurul Amira (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Mission and vision statements are important aspects of the strategic management process for an organization. A well-prepared vision and mission statement would differentiate one organization from another by displaying its distinctive feature and future directions that differentiates it from the others. The best mission and vision contribute to the high business performance, which would benefit the stakeholders. The establishment of the mission and vision statements give direction for companies and to inspire everyone is working towards a common objective and set the goal for the strategic growth.